Thermophysical correlation of hybrid nanofluids (HNFS) : A thematic review - Masyfu'ah, Mokhtar; Abdul Rahman, Mohd Kasim; Iskandar, Waini; Nur Syahidah, Nordin; Mohammed Al-Sharifi, Hussein Ali (Semarak Ilmu Publishing, 2024)
Hybrid nanofluids represent innovative fluid class that combine the advantages of nanoparticles with base fluid to enhance the heat transfer capabilities. It exhibits higher heat transfer capabilities compared to traditional nanofluids. Researchers have seized abundant opportunity to further investigate the unknown behaviour of hybrid nanofluids over different geometries and physical parameters numerically by implementing a certain model of correlation. However, from the literature, these correlation models sometimes underestimate the experimental data of thermal performance. Thus, it is crucial for this review paper to discuss these models for advancing research in this field. Utilizing keyword search and filtering parameters, 354 journal articles from the Scopus and Web of Science (WoS) databases were found. Following the application of the inclusion and exclusion criteria process, only 60 papers were evaluated as final articles. These studies were further classified into seven types of correlations: Devi, Modified Devi Type A, Modified Devi Type B, Modified Devi Type C, Takabi, Modified Takabi and Xue model. It is found that Xue model is widely used for solving hybrid nanofluids flow problem which dealing with carbon nanotube particle. While Devi and Takabi-based model are extensively used for non-carbon nanotube particle. This study provides valuable insights for future research to further study the hybrid nanofluid flow precisely and increase the heat transfer performance.